Identification of Residues in the Lipopolysaccharide ABC Transporter That Coordinate ATPase Activity with Extractor Function - Brent W. Simpson (American Society for Microbiology, 2016)
ABSTRACT The surface of most Gram-negative bacteria is covered with lipopolysaccharide (LPS), creating a permeability barrier against toxic molecules, including many antimicrobials. To assemble LPS on their surface, Gram-negative bacteria must extract newly synthesized LPS from the inner membrane, transport it across the aqueous periplasm, and translocate it across the outer membrane. The LptA to -G proteins assemble into a transenvelope complex that transports LPS from the inner membrane to the cell surface. The Lpt system powers LPS transport from the inner membrane by using a poorly characterized ATP-binding cassette system composed of the ATPase LptB and the transmembrane domains LptFG. Here, we characterize a cluster of residues in the groove region of LptB that is important for controlling LPS transport. We also provide the first functional characterization of LptFG and identify their coupling helices that interact with the LptB groove. Substitutions at conserved residues in these coupling helices compromise both the assembly and function of the LptB2FG complex. Defects in LPS transport conferred by alterations in the LptFG coupling helices can be rescued by changing a residue in LptB that is adjacent to functionally important residues in the groove region. This suppression is achieved by increasing the ATPase activity of the LptB2FG complex. Taken together, these data identify a specific binding site in LptB for the coupling helices of LptFG that is responsible for coupling of ATP hydrolysis by LptB with LptFG function to achieve LPS extraction. IMPORTANCE Lipopolysaccharide (LPS) is synthesized at the cytoplasmic membrane of Gram-negative bacteria and transported across several compartments to the cell surface, where it forms a barrier that protects these organisms from antibiotics. The LptB2FG proteins form an ATP-binding cassette (ABC) transporter that uses energy from ATP hydrolysis in the cytoplasm to facilitate extraction of LPS from the outer face of the cytoplasmic membrane prior to transport to the cell surface. How ATP hydrolysis is coupled with LPS release from the membrane is not understood. We have identified residues at the interface between the ATPase and the transmembrane domains of this heteromeric ABC complex that are important for LPS transport, some of which coordinate ATPase activity with LPS release.